A Systematic Review of Master's Theses on Surgical Nursing Conducted in Northern Cyprus - Gülcan Dürüst Sakallı; Serpil Çağlayan Payas; Kerem Yıldız; Gülten Sucu Dağ; Sevinç Taştan (Galenos Publishing House, 2022)
This systematic review aims to analyze master's theses on surgical nursing, which were conducted in the Turkish Republic of Northern Cyprus between 2010 and 2021. This study reviewed the master's theses on the databases of the Council of Higher Education (YÖK) and the universities in the Turkish Republic of Northern Cyprus, which offered a master's degree in nursing. Using the keywords surgical nursing, nursing, and master's thesis, we identified 37 theses that met the inclusion criteria and classified these theses according to aim, sample, clinic, year of publication, the title of advisor, and the department of study. About 70.3% of the theses were conducted between 2016 and 2021, 59.7% were conducted on healthy individuals, 96% had a descriptive design, and 42.85% used scales to collect data. This systematic review found that the number of master's studies on surgical nursing significantly increased in the last decade. Nearly all theses had a descriptive design, and the majority of the studies were conducted on healthy participants.